German principals’ attitude towards the form of religious education at state schools - Riegel, Ulrich (Journal of Religious Education, 2020)
Despite the strong status of denominational religious education (RE) in the German constitution this organizational form of RE finds itself increasingly under pressure at state schools. Reasons for this development are among others the shrinking percentage of baptized people in Germany, problems in organising this form of RE at school and the discussion on the role of religion in civil society. Concerning the future of RE four options can be determined that need to be discussed: denominational RE, cooperative RE, integrative RE and Moral Education instead of RE. This article presents a survey of 228 school principals who have introduced a cooperative RE at their school to find out which form of RE they prefer for which reasons. The results show that they prefer integrative RE (M = 4.07) over cooperative RE (M = 4.00). Moral Education does not get much support (M = 2.57), but still more than denominational RE (M = 2.27). Regression analysis gives evidence that issues like organizational aspects (for example size of the school) and educational goals (for example views on “taking position in RE”) predict the principals’ preferences. These results provide first impressions of an important group of people within the educational system who have hardly been considered in the discussion about how religion should be taught in the future.